Luminescence of the NaCl matrix under local and elastic deformation - Убаев , Ж.; Шункеев, К.; Мясникова , Л.; Сагимбаева , Ш. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article analyzes the X-ray luminescence spectra at low-temperature (90K) elastic deformation ( ε =0.9%) of high purity NaCl (zone-purified), NaCl-Li (0.2 mol%) and natural NaCl (Halite) crystals. It has been found that, in the NaCl matrix, the self-trapping of excitons in regular lattice sites is activated at a decrease in the symmetry of the lattice by the elastic deformation, and the transfer of exciton energy to impurities is significantly impaired. In the NaCl (Halite) crystal, the applied elastic deformation suppresses the luminescence with a maximum at 3.95 eV associated with impurity bromine (Br) ions. The experimental results allow elastic deformation to be used as an experimental method for separating intrinsic and impurity luminescence of crystals.